Integrated Production Planning and Scheduling Optimization - Daniel Filipe de Almeida Carvalho (2019)
This work proposes an iterative solution method to address the integration of the tactical (lot-sizing) and operational (scheduling) levels in production planning with sequence dependent setups. This method breaks the integrated lot-sizing and scheduling problem into two. In the first sub-problem, at the tactical level, the production plan is optimized with production setups disregarded. The production scheduling solution is then defined using local search strategies that will also construct rules for the tactical level. After that, the tactical level is optimized again, considering the rules defined from the operational level. The algorithm continues iteratively until objective functions from both levels converge. In order to analyse results, two computational experiments are proposed. The first is performed to compare the solution method proposed with mixed-integer programming models and meta-heuristics from the literature. Then the research will focus on an animal-feed industry case, in which production setup is sequence dependent and usually presents non-triangular setups, so products can avoid cleaning setups if produced between two products that otherwise would require a setup. The purpose of the second experiment is to evaluate the potential gains to a hierarchical approach usually used in this industry.